IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI KEGIATAN KOKURIKULER DALAM PERSPEKTIF KURIKULUM MERDEKA DI SEKOLAH DASAR - Lulu' Arifatun Munasiroh; Iqbal Yulianto; Eka Titi Andaryani; Sri Sumartiningsih; Philip X. Fuchs (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of character education through co-curricular activities within the framework of the Merdeka Curriculum in elementary schools. This research employs a qualitative approach with a descriptive design. The study was conducted at SD Nasima, with research subjects consisting of the vice principal for student affairs, teachers, and students. Data were collected through interviews, observations, and documentation. The data analysis utilized an interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the implementation of co-curricular activities has been carried out systematically through the stages of planning, implementation, and evaluation. These activities contribute to the development of character values such as religiosity, discipline, responsibility, cooperation, and creativity through contextual and participatory learning experiences. Furthermore, co-curricular activities are closely aligned with the dimensions of the Pancasila Student Profile, thereby supporting the development of students who are both morally grounded and globally competitive. Supporting factors include school policies, active teacher involvement, and adequate facilities, while inhibiting factors consist of time constraints, varying levels of teacher understanding, and suboptimal program management. In conclusion, co-curricular activities play a strategic role in strengthening character education in elementary schools. Therefore, continuous efforts are needed to improve planning, implementation, and evaluation processes, as well as to enhance teacher competence to ensure more effective and sustainable implementation.Keywords: Character education, Co-curricular activities, Merdeka curriculum